ASSESSMENT OF KNOWLEDGE REGARDING BREAST SELF EXAMINATION AMONG NURSING STUDENTS IN TERTIARY CARE SETTING - BARKAT, A; AFZAL, A; IQBAL, H; ZUNAIRA, .; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Breast cancer is the leading cause of cancer-related morbidity and mortality among women worldwide, with a high prevalence in Pakistan. Breast Self-Examination (BSE) is a cost-effective tool for early detection, yet awareness and practices remain suboptimal in low-resource settings. Objective: This study assesses the knowledge and practices of nursing students regarding BSE in a tertiary care setting in Pakistan. Methods: A descriptive cross-sectional study was conducted among 160 nursing students at a tertiary care hospital in Lahore, Pakistan. Convenience sampling was used, and data were collected using a structured questionnaire. The instrument assessed demographic characteristics, awareness of breast cancer and BSE, and practices related to its frequency and technique. Data were analyzed using SPSS version 26, with descriptive and inferential statistics applied. Results: The study revealed that 87.5% of participants were aware of breast cancer prevalence, and 81.25% had heard of BSE. Most participants (62.5%) correctly identified the recommended monthly frequency for performing BSE, and 81.25% demonstrated knowledge of the correct technique. Informal sources, such as home (31.25%) and TV/radio (25.0%), were the primary channels for BSE knowledge. Significant gaps in formal education and technical accuracy were identified, particularly among junior students. Conclusion: Although nursing students demonstrated a relatively high awareness of BSE, deficiencies in formal training and technical knowledge underscore the need for enhanced breast health education in nursing curricula. Addressing these gaps through structured educational interventions can improve BSE practices and empower nursing students as agents of change in promoting breast cancer awareness in Pakistan.